2000
DOI: 10.1111/j.1540-8167.2000.tb00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Exit Block of Focal Repetitive Activity in the Superior Vena Cava Masquerading as a High Right Atrial Tachycardia

Abstract: An unusual case of atrial tachycardia (AT) originating from the superior vena cava (SVC) is reported. A 34-year-old man without structural heart disease underwent catheter ablation for drug-resistant AT. During the tachycardia, low-amplitude spiky electrograms with a cycle length of 120 to 175 msec were recorded in the SVC and exhibited 2:1 exit block to the atria, masquerading as the atrial activation observed with high right AT. These spiky electrograms also were observed during sinus rhythm, but they appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] More recently, Ino et al described a case with a 2:1 exit block of repetitive focal activity in a SVC focus manifesting as a high right AT. 13 Furthermore, we found that AT can occur focally from different parts of the SVC, which was confirmed by the SVC angiogram showing the location of the successful ablation sites at various distances above the atriocaval junction and different positions within the SVC (Fig 7). These SVC foci were all located within 30 mm above from the atriocaval junction, which is in accordance with the histological and electrical connections of the musculature between the SVC and the right atrium.…”
Section: Discussionsupporting
confidence: 71%
“…[1][2][3][4][5][6][7][8] More recently, Ino et al described a case with a 2:1 exit block of repetitive focal activity in a SVC focus manifesting as a high right AT. 13 Furthermore, we found that AT can occur focally from different parts of the SVC, which was confirmed by the SVC angiogram showing the location of the successful ablation sites at various distances above the atriocaval junction and different positions within the SVC (Fig 7). These SVC foci were all located within 30 mm above from the atriocaval junction, which is in accordance with the histological and electrical connections of the musculature between the SVC and the right atrium.…”
Section: Discussionsupporting
confidence: 71%
“…Conduction block between the atrium and thoracic veins has been reported and is well recognized in the pulmonary veins; however, conduction block from the SVC to the right atrium (RA) is rare [3,5]. In this case, a conduction block at the exit site of the SVC-RA connection was strongly suggested using a circular multipolar catheter (Lasso) and CARTO mapping.…”
Section: Introductionmentioning
confidence: 78%
“…11,34) In the right atrium, common locations of AT origins are the crista terminalis, right-side of the interatrial septum including the vicinity of the AV node, right atrial appendage, tricuspid annulus, coronary sinus ostium, and the SVC. 11,26,[34][35][36][37][38][39][40][41][42] In the left atrium, AT origin tend to cluster the pulmonary vein ostium, the left atrial appendage, left-side of the interatrial septum, the coronary sinus body, mitral annulus, the ligament of Marshall, or a left-sided SVC.…”
Section: Anatomymentioning
confidence: 99%
“…60) Electrical isolation of the SVC can cure tachycardias originating from the SVC muscle sleeve despite continued focal electrical activity inside the sleeve. 40) Ablation of pulmonary vein tachycardia that targets the ectopic focus is highly effective. However, electrical disconnection of the arrhythmogenic pulmonary vein at the atria -pulmonary vein junction may be a preferable approach in some cases to avoid a risk of pulmonary vein stenosis.…”
Section: Ablation Techniquesmentioning
confidence: 99%